THE SYSTEMS APPROACH TO THE STUDY OF TECHNOLOGICAL PROCESS OF HARVESTING FLAX - Примаков, О. А. (Scientific Progress & Innovations, 2013)
The article reveals the issues of a rational scheme of harvesting flax with the use of agricultural machines for general use. The adequate selection of the necessary and sufficient technical operations for flax harvesting on new technology has been done. When choosing machines for the harvesting of flax a great attention is paid not to special flax pullers but to equipment that is used to harvest other crops, making the technology more accessible to a wide range of manufacturers.